The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1516-4446-2014-1629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of REM sleep restriction during pregnancy on rodent maternal behavior

Abstract: Objective: To evaluate the effects of sleep restriction during pregnancy on maternal care and maternal aggression in a rodent model. Methods: Twenty-three female Wistar rats were assigned to one of two groups: control (n=12) or sleep restriction (n=11) during the entire pregnancy. At the fifth postpartum day, the animals were subjected to the resident-intruder paradigm and to the pup retrieval test. Results: Sleep restriction during pregnancy had no direct effects on maternal care. Regarding aggressive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…These findings suggest that sleep deprivation lowers the threshold of interoceptive sensitivity of brain homeostatic systems, enhancing the threat-response system and affecting the interpretation of pro-social and antisocial cues (Goldstein-Piekarski et al, 2015, Simon et al, 2015). Findings from the animal literature are also supportive of this model, suggesting that deprivation of rapid eye movement sleep in pregnant rats increases defensive aggression and reduces the threshold for responding to potentially hostile stimuli (Pires et al, 2015). Overall, our findings are consistent with these data in animals and humans, suggesting that the accuracy of detecting facial displays that communicate clear and present danger may be more robust against sleep deprivation than those involved in detecting social and affiliative emotions.…”
Section: Discussionmentioning
confidence: 93%
“…These findings suggest that sleep deprivation lowers the threshold of interoceptive sensitivity of brain homeostatic systems, enhancing the threat-response system and affecting the interpretation of pro-social and antisocial cues (Goldstein-Piekarski et al, 2015, Simon et al, 2015). Findings from the animal literature are also supportive of this model, suggesting that deprivation of rapid eye movement sleep in pregnant rats increases defensive aggression and reduces the threshold for responding to potentially hostile stimuli (Pires et al, 2015). Overall, our findings are consistent with these data in animals and humans, suggesting that the accuracy of detecting facial displays that communicate clear and present danger may be more robust against sleep deprivation than those involved in detecting social and affiliative emotions.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, some articles have already evaluated grooming following sleep deprivation (Andersen et al, 2005;Nunes et al, 2012;Pires et al, 2012a;Pires et al, 2013Pires et al, , 2015a. In respect of the methods currently available to evaluate grooming behavior, one could think of three possible alternatives: the classical evaluation by latency, frequency and duration of this behavior (Andersen et al, 2005); the use of self-cleaning indexes (Nunes et al, 2012) and the use of the grooming analysis algorithm Tuohimaa, 2004, 2005a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal care is crucial for the adequate development of the pups and this type of behavior can be classified as any action taken by the mother in order to nourish, soothe and protect the pups (Kristal, 2009;Pires, Tufik, & Andersen, 2015). In addition to provide nutrition and safety, it is essential to ensure the necessary stimuli for development (Caldji et al, 1998;Meaney, 2001), since it was already been observed that variations in the maternal behavior (MB) can modulate the neuroendocrine and psychological development, as well as the responses to stress (Francis, Diorio, Liu, & Meaney, 1999;Nephew & Murgatroyd, 2013;Weaver et al, 2004).…”
Section: Abstract: Early Life Stress; Maternal Behavior; Maternal Sepmentioning
confidence: 99%
“…The behaviors N, L, C and R were categorized as maternal behaviors because they impact directly on the pup, and can provide physical and emotional care (Pires et al, 2015). Furthermore, no interaction with the pups (X) and eating/drinking (E) were considered as behaviors not related with maternal care.…”
Section: Maternal Behaviormentioning
confidence: 99%